Analyzing Eighth-Grade Students' Mathematical Communication Skills in Solving Exponential Problems - Ode, Windi Saputri; Salido, Achmad; Sirad, La Ode; Haidar, Irajuana; Prihatmojo, Agung; Husain, Dayana Sabila; Wangsa, Arma (Universitas Lampung, 2024)
This study examines the mathematical communication skills of eighth-grade students in solving exponential problems. Effective mathematical communication enables students to articulate ideas clearly through writing, drawings, or symbols. A descriptive qualitative method was used, involving three students with high, medium, and low math abilities. Data were collected via problem-solving tasks and semi-structured interviews to analyze students' strategies and thought processes. Results revealed notable differences in skills: high-ability students developed accurate models but lacked consistency, medium-ability students had a sufficient foundation but struggled with contextual interpretation, and low-ability students relied on basic operations without grasping the problem's context. These findings emphasize the need for adaptive learning approaches tailored to students' abilities to enhance mathematical communication. Study limitations include a small sample size and narrow topic focus. Future research should explore broader samples and topics to deepen insights, contributing to the development of more responsive math teaching methods that effectively foster mathematical communication skills.